INNOVATIVE APPROACHES TO YOUTH ENTREPRENEURSHIP CONSULTING (Innovative professional education, 2025)
The article examines the features of youth entrepreneurship consulting at the Chernivtsi High School of Commerce of the State University of Trade and Economics. It outlines modern trends in youth entrepreneurship consulting and explores innovative approaches. Effective methods for developing an entrepreneurial mindset are identified, including participation in Entrepreneurship Camps and Youth Entrepreneurship EXPO Fairs. The main directions and forms of work of the College’s Career Development Center are analyzed, where consultants provide informational and other services on the types of entrepreneurship, options, and ways to start a business
Keywords: youth entrepreneurship, entrepreneurial skills, career consultants, business cases, Career Development Center